Hydrogen evolution electrode and preparation method and application thereof

By loading ruthenium-based nanocatalysts and hydrophobic polymers on the surface of the conductive substrate, a high-efficiency hydrogen evolution electrode was prepared, which solved the problems of high overpotential, insufficient catalyst activity and poor electrode stability in the prior art, and achieved high current density and low energy consumption Hydrogen production effect by electrolysis of water.

CN119392281APending Publication Date: 2025-02-07ARCTECH SOLAR HOLDING CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411536437.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-31
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

In the existing water electrolysis hydrogen production technology, the high overpotential of the hydrogen evolution reaction, insufficient catalyst activity, low current density and poor electrode stability limit the large-scale application of the technology.

Method used

By uniformly loading the ruthenium-based nanocatalyst on the surface of the conductive substrate and introducing hydrophobic polymers, using multi-layer coating technology and high-temperature heat treatment, an efficient hydrogen evolution electrode was prepared.

Benefits of technology

The catalytic reaction activity and stability of the hydrogen evolution electrode is significantly improved, the electrolytic current density is improved, the overall energy consumption of the electrolytic cell is reduced, and the mechanical strength and chemical stability of the electrode are enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119392281A_ABST
    Figure CN119392281A_ABST
Patent Text Reader

Abstract

The invention relates to a hydrogen evolution electrode and a preparation method and application thereof, and the preparation method comprises the following steps: preparing an active component solution containing tris (2, 2 '-dipyridyl) ruthenium dichloride; repeatedly brushing the active component solution on the surface of a conductive substrate for multiple times, and performing vacuum drying at a certain temperature after each brushing to form a multi-layer coating structure; carrying out heat treatment in an inert atmosphere to obtain a hydrogen evolution electrode; according to the preparation method of the hydrogen evolution electrode, through introduction of the efficient ruthenium-based catalyst and hydrophobicity regulation and control, the remarkable technical effects of improving the catalytic activity and the current density of the electrode, reducing energy consumption, enhancing stability and the like are achieved, and meanwhile the technology has wide application potential due to the fact that the technology is simple and suitable for industrial production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of electrocatalytic hydrogen production, and in particular relates to a hydrogen evolution electrode and a preparation method and application thereof. Background Art

[0002] Hydrogen has become a favorable alternative to traditional energy due to its high energy density, green and renewable characteristics. Hydrogen production by water electrolysis has been reported as a sustainable and advanced technology due to its high efficiency and high purity products. However, existing water electrolysis technology still faces a series of challenges in practical applications, especially the high overpotential of the hydrogen evolution reaction, which greatly increases the energy consumption of the electrolyzer and limits the large-scale application of water electrolysis hydrogen production technology.

[0003] Currently, the cathode of alkaline electrolyzers usually uses Raney nickel as a catalyst to reduce the overpotential of the hydrogen evolution reaction. However, the Raney nickel catalyst still has problems of low current density and high overall energy consumption during application. In addition, the stability of existing electrode materials is relatively poor, and performance degradation or catalyst shedding is prone to occur during long-term operation, resulting in a decrease in hydrogen evolution efficiency. Summary of the invention

[0004] In view of at least one of the technical problems of high overpotential, insufficient catalyst activity, low current density and poor electrode stability in the current water electrolysis hydrogen production technology, the present invention provides a hydrogen evolution electrode and a preparation method and application thereof, wherein a ruthenium-based nanocatalyst is uniformly loaded on the surface of a conductive substrate through a multi-layer coating technology, thereby improving the catalytic reaction activity and stability of the hydrogen evolution electrode as a whole, greatly increasing the electrolysis current density, and reducing the overall energy consumption of the electrolyzer.

[0005] According to one aspect of the present invention, there is provided a method for preparing a hydrogen evolution electrode, comprising the following steps:

[0006] preparing an active component solution containing tris(2,2'-bipyridyl)ruthenium dichloride;

[0007] Repeatedly brushing the active component solution on the surface of the conductive substrate for multiple times, and vacuum drying at a certain temperature after each brushing to form a multi-layer coating structure;

[0008] The hydrogen evolution electrode is obtained by heat treatment under an inert atmosphere.

[0009] In some technical solutions, the active component solution is prepared by dissolving the active component of tris(2,2'-bipyridine)ruthenium dichloride in an appropriate amount of solvent, and the concentration of tris(2,2'-bipyridine)ruthenium dichloride obtained is 0.03-0.3 mol / L;

[0010] The solvent comprises deionized water, glycerol, solvent A and solvent B, wherein the solvent A and solvent B are respectively selected from any one of ethanol, isopropanol, n-butanol, tetrahydrofuran, acetone, ethyl acetate and ethylene glycol, and the preparation volume ratio of the deionized water, glycerol, solvent A and solvent B is 1-4:0.1-1:1-2:1-2.

[0011] In the above scheme, the concentration of tris(2,2'-bipyridine)ruthenium dichloride is 0.03-0.3 mol / L, which specifically means: when preparing the active component solution, after deionized water, ethanol, isopropanol, glycerol, etc. are mixed as an organic solvent, the volume of the organic solvent is measured, and then the appropriate concentration value is determined within the concentration range of tris(2,2'-bipyridine)ruthenium dichloride, and the added mass is calculated based on the volume and concentration value.

[0012] In the above scheme, in the organic solution, deionized water and glycerol are essential items, and any two of n-butanol, tetrahydrofuran, acetone, ethyl acetate, and ethylene glycol can replace ethanol and isopropanol, and the ratio range after replacement is the same as the above range, wherein the role of glycerol is to adjust the viscosity of the organic solution, thereby adjusting the fluidity.

[0013] In some technical solutions, the active component solution further contains 1 wt% to 10 wt% of a hydrophobic polymer.

[0014] The hydrophobic polymer is polytetrafluoroethylene or polyvinylidene fluoride dissolved in N,N-dimethylformamide.

[0015] In the above scheme, polytetrafluoroethylene is preferably a purchased suspension product with a polytetrafluoroethylene content of 60wt%. The polytetrafluoroethylene suspension is not a necessary item for preparing the active component solution. For example, in Example 3, the electrode substrate is a nickel mesh, and a 46-mesh nickel mesh is selected because its pore size is relatively large and it is not a three-dimensional structure, so the gas itself is easier to pass through, so polytetrafluoroethylene is not needed to increase the hydrophobicity.

[0016] In the above scheme, the concentration of polytetrafluoroethylene is 1wt% to 10wt%, which specifically means that when preparing the active component solution, after deionized water, ethanol, isopropanol, glycerol, etc. are mixed into an organic solvent, the weight of the organic solvent is measured, and then a suitable concentration value is selected within the concentration range of polytetrafluoroethylene. The weight of the polytetrafluoroethylene is calculated based on the weight and concentration value of the organic solvent. If the concentration of polytetrafluoroethylene in the polytetrafluoroethylene suspension is known, such as a suspension with a polytetrafluoroethylene content of 60wt%, after the weight of the polytetrafluoroethylene is calculated, the weight of the polytetrafluoroethylene suspension to be added can be calculated based on the concentration value of the polytetrafluoroethylene in the polytetrafluoroethylene suspension.

[0017] In some technical solutions, the vacuum drying temperature is 60-100° C., the duration is 2-5 hours, and the number of brushing times is 5-10 times; and / or,

[0018] The heat treatment is performed at a temperature of 400° C. to 900° C. and for a duration of 2 to 10 hours.

[0019] Some technical solutions also include a cleaning step for the conductive substrate:

[0020] The conductive substrate is ultrasonically cleaned with appropriate amounts of sulfuric acid, anhydrous ethanol, and deionized water in sequence, and then vacuum dried for later use.

[0021] In some technical solutions, the concentration of sulfuric acid is 0.1-1 mol / L, each ultrasonic cleaning lasts for 5-20 minutes, the drying temperature after cleaning is 60-100° C., and the drying time is 1-5 hours.

[0022] In some technical solutions, the conductive substrate is selected from any one of nickel mesh, nickel foam, sintered nickel plate and nickel felt.

[0023] The preparation method of the hydrogen evolution electrode in the present application shows remarkable technical effects in improving the catalytic activity and current density of the electrode, reducing energy consumption, and enhancing stability by introducing a highly efficient ruthenium-based catalyst and regulating hydrophobicity. At the same time, due to its simple process and suitability for industrial production, the technology has broad application potential, especially in large-scale hydrogen production technology.

[0024] According to another aspect of the present invention, there is provided a hydrogen evolution electrode obtained according to the above-mentioned preparation method, wherein the hydrogen evolution electrode is supported by a nickel substrate, and a ruthenium-based nanocatalyst is uniformly loaded on the surface by a multi-layer coating technology.

[0025] In some technical solutions, a hydrophobic polymer is also introduced into the surface coating of the hydrogen evolution electrode to form a microscopic hydrophobic channel structure inside the electrode. According to another aspect of the present invention, there is further provided an application of a hydrogen evolution electrode in hydrogen production by electrolysis of water, wherein the above-mentioned hydrogen evolution electrode or the hydrogen evolution electrode prepared by the above-mentioned preparation method is used as a cathode in an alkaline medium to electrolyze water to decompose hydrogen gas.

[0026] The present invention adopts the above technical solution to have at least one of the following beneficial effects:

[0027] 1. The present invention provides a hydrogen evolution electrode and a preparation method and application thereof. By introducing a ruthenium-based nanocatalyst, the catalytic performance of the hydrogen evolution reaction is significantly improved. Ruthenium, as a platinum group noble metal, has excellent catalytic activity, can effectively reduce the overpotential of the hydrogen evolution reaction, reduce the energy required in the reaction process, and ultimately significantly reduce the energy consumption of the electrolytic cell; at the same time, it can also effectively enhance the rate of the hydrogen evolution reaction, thereby significantly improving the electrolysis current density; and the uniform distribution of ruthenium nanoparticles increases the specific surface area of ​​the electrode, so that more catalytic sites can participate in the reaction, further improving the catalytic activity;

[0028] 2. The present invention provides a hydrogen evolution electrode and a preparation method and application thereof. By introducing a hydrophobic polymer (such as polytetrafluoroethylene), the method effectively regulates the hydrophilicity and hydrophobicity of the electrode, optimizes the discharge path of the gas (hydrogen) generated during the hydrogen evolution reaction, and the hydrophobic channel structure inside the electrode helps the gas to be quickly discharged from the electrode surface, reduces the bubble retention phenomenon, prevents bubbles from blocking the active sites, and ensures the continuous and efficient conduct of the hydrogen evolution reaction;

[0029] 3. The present invention provides a hydrogen evolution electrode and a preparation method and application thereof. The preparation method has a simple process, a short flow, and a low total cost, and is very suitable for large-scale industrial production. Conventional nickel-based materials are used as substrates, and ruthenium-based catalysts and hydrophobic polymers are coated thereon, so that large-scale production of electrodes can be achieved at a low cost, meeting actual production needs.

[0030] 4. The present invention provides a hydrogen evolution electrode and a preparation method and application thereof. During the preparation process, the catalyst and the electrode substrate are subjected to high-temperature heat treatment to form a strong chemical bond, thereby enhancing the mechanical strength and chemical stability of the electrode; the catalyst is firmly attached to the surface of the substrate, avoiding the falling off of the catalyst during long-term electrolysis operation, and improving the service life of the electrode. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the following briefly introduces the drawings required for use in the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0032] Figure 1 This is a process flow chart of the preparation of the hydrogen evolution electrode described in Examples 1-3 of the present invention;

[0033] Figure 2 The graph is a performance test result diagram of hydrogen evolution electrodes of Examples 1-3 of the present invention and Comparative Example 1;

[0034] Figure 3This is a comparison chart of the performance test results of Example 1 of the present invention and Comparative Example 2;

[0035] Figure 4 This is a scanning electron microscope image of the hydrogen evolution electrode prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0036] The present invention will be further described below in conjunction with specific examples. It should be understood that these examples are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms also fall within the scope limited by the appended claims of the present application. The various commonly used reagents used in the examples are all commercially available products.

[0037] like Figure 1 , showing the preparation process of the hydrogen evolution electrode of the present application, with specific reference to Examples 1-3.

[0038] Example 1

[0039] (1) Preparing an active component solution: 25 ml of ethanol and 25 ml of isopropanol are measured and mixed; 6 g of tris(2,2'-bipyridine)ruthenium dichloride is weighed and dissolved in 50 ml of the mixed solution of ethanol and isopropanol, and stirred evenly; 50 ml of deionized water, 2.5 ml of glycerol and 1.7 g of 60 wt% polytetrafluoroethylene suspension are added to the above solution in sequence, stirred evenly, and set aside.

[0040] According to the molar calculation formula, the molar mass of a substance (M) = mass of the substance (m) / amount of the substance (n), unit: g / mol, the relative molecular mass of tris(2,2'-bipyridine) ruthenium dichloride is 640.53g / mol, so the molar mass of tris(2,2'-bipyridine) ruthenium dichloride (M) = mass (m) / 640.53, after converting the molar mass of tris(2,2'-bipyridine) ruthenium dichloride, divide it by the volume of the solvent to get the concentration of tris(2,2'-bipyridine) ruthenium dichloride.

[0041] In this embodiment, the mass of tris(2,2'-bipyridine)ruthenium dichloride is 6g, so the molar mass of tris(2,2'-bipyridine)ruthenium dichloride is 6 / 640.53≈0.01mol, and the volume of the solution is about 102.5ml, so the concentration value of tris(2,2'-bipyridine)ruthenium dichloride is: 0.01÷(102.5÷1000)=0.098mol / L. The concentration conversion of the remaining embodiments is the same as the above idea, which will not be repeated here.

[0042] (2) Electrode substrate pretreatment: nickel felt was used as the electrode substrate, and it was placed in 0.5 mol / l sulfuric acid, anhydrous ethanol, and deionized water in turn, and ultrasonically cleaned for 15 min; the cleaned nickel felt was placed in a vacuum drying oven and vacuum dried at 80°C for 2 h.

[0043] (3) Applying the active component solution by brushing: Dip a brush into the prepared active component solution, apply it to the surface of the nickel felt, and then place it in a vacuum drying oven and vacuum dry it at 80°C for 2 hours. After drying, use a brush to apply the active component solution to the surface of the nickel felt again, and then vacuum dry it again. Repeat this process 5 times.

[0044] (4) High temperature heat treatment: The nickel felt coated with the active component solution was placed in an argon atmosphere and heat treated at 400°C for 2 hours. The prepared electrode was used as the cathode and the cleaned nickel foam was used as the anode to assemble the electrolytic cell for performance testing. The test environment was 30wt% KOH solution at 80°C.

[0045] like Figure 4 , is a scanning electron microscope image of the prepared hydrogen evolution electrode. It can be seen that the ruthenium nanoparticles are evenly distributed, which significantly increases the specific surface area of ​​the electrode, allowing more catalytic sites to participate in the reaction and improving the catalytic activity.

[0046] Example 2

[0047] (1) Preparing an active component solution: 50 ml of ethanol and 50 ml of isopropanol were measured and mixed; 10 g of tris(2,2'-bipyridine)ruthenium dichloride was weighed and dissolved in 100 ml of the mixed solution of ethanol and isopropanol, and stirred evenly; 100 ml of deionized water, 5 ml of glycerol and 3.4 g of 60 wt% polytetrafluoroethylene suspension were added to the above solution in sequence and stirred evenly.

[0048] (2) Electrode substrate pretreatment: nickel foam was used as the electrode substrate, which was placed in 0.5 mol / l sulfuric acid, anhydrous ethanol, and deionized water in turn, and ultrasonically cleaned for 15 min; the cleaned nickel foam was placed in a vacuum drying oven and vacuum dried at 80°C for 4 h.

[0049] (3) Applying the active component solution by brushing: Dip a brush into the prepared active component solution, apply it to the surface of the nickel foam, and then place it in a vacuum drying oven and vacuum dry it at 80°C for 4 hours. After drying, use a brush to apply the active component solution to the surface of the nickel foam again, and then vacuum dry it again. Repeat this process 5 times.

[0050] (4) High temperature heat treatment: The nickel foam coated with the active component solution was placed in an argon atmosphere and heat treated at 400°C for 2 hours. The prepared electrode was used as the cathode and the cleaned nickel foam was used as the anode to assemble the electrolytic cell for performance testing. The test environment was 30wt% KOH solution at 80°C.

[0051] Example 3

[0052] (1) Prepare active component solution: measure 50 ml of ethanol and 50 ml of isopropanol respectively and mix them; weigh 8 g of tris(2,2'-bipyridine)ruthenium dichloride and dissolve it in 100 ml of the mixed solution of ethanol and isopropanol, and stir evenly; add 70 ml of deionized water and 3.5 ml of glycerol to the above solution in sequence and stir evenly for use.

[0053] (2) Electrode substrate pretreatment: A nickel mesh was used as the electrode substrate, which was placed in 0.5 mol / l sulfuric acid, anhydrous ethanol, and deionized water in turn, and ultrasonically cleaned for 15 min; the cleaned nickel mesh was placed in a vacuum drying oven and vacuum dried at 80°C for 1 h.

[0054] (3) Applying the active component solution by brushing: Dip a brush into the prepared active component solution, apply it to the surface of the nickel mesh, and then place it in a vacuum drying oven and vacuum dry it at 80°C for 2 hours. After drying, use a brush to apply the active component solution to the surface of the nickel mesh again, and then vacuum dry it again. Repeat this process 5 times.

[0055] (4) High temperature heat treatment: The nickel mesh coated with the active component solution was placed in an argon atmosphere and heat treated at 400°C for 2 hours. The prepared electrode was used as the cathode and the cleaned nickel foam was used as the anode to assemble the electrolytic cell and perform performance testing. The test environment was 30wt% KOH solution at 80°C.

[0056] Comparative Example 1

[0057] The cleaned nickel foam was used as cathode and anode to assemble an electrolytic cell and perform a performance test in a 30wt% KOH solution at 80°C.

[0058] Comparative Example 2

[0059] (1) Prepare active component solution: measure 25 ml of ethanol and 25 ml of isopropanol respectively and mix them; weigh 6 g of tris(2,2'-bipyridine)ruthenium dichloride and dissolve it in 50 ml of the mixed solution of ethanol and isopropanol, and stir evenly; add 50 ml of deionized water and 2.5 ml of glycerol to the above solution in sequence, stir evenly, and set aside.

[0060] (2) Electrode substrate pretreatment: nickel felt was used as the electrode substrate, and it was placed in 0.5 mol / l sulfuric acid, anhydrous ethanol, and deionized water in turn, and ultrasonically cleaned for 15 min; the cleaned nickel felt was placed in a vacuum drying oven and vacuum dried at 80°C for 2 h.

[0061] (3) Applying the active component solution by brushing: Dip a brush into the prepared active component solution, apply it to the surface of the nickel felt, and then place it in a vacuum drying oven and vacuum dry it at 80°C for 2 hours. After drying, use a brush to apply the active component solution to the surface of the nickel felt again, and then vacuum dry it again. Repeat this process 5 times.

[0062] (4) High temperature heat treatment: The nickel felt coated with the active component solution was placed in an argon atmosphere and heat treated at 400°C for 2 hours. The prepared electrode was used as the cathode and the cleaned nickel foam was used as the anode to assemble the electrolytic cell for performance testing. The test environment was 30wt% KOH solution at 80°C.

[0063] The performance test results of Examples 1-3 and Comparative Example 1 are as follows Figure 2 As shown;

[0064] The performance curves of Example 1 and Comparative Example 2 are plotted together for comparison. Figure 3 shown.

[0065] It can be seen that the catalytic performance of the hydrogen evolution electrode in this scheme is significantly improved compared with the comparative example, especially the electrode using ruthenium-based nanocatalyst and hydrophobicity regulation can significantly reduce the overpotential at the same current density, or in other words, the current density can be significantly increased under the same overpotential, especially the use of ruthenium-based nanocatalyst, and has better gas mass transfer capacity. The test curve shows that the electrode after catalyst treatment exhibits excellent hydrogen evolution reaction performance under different conditions, which meets the needs of industrial applications.

[0066] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the present invention. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the present invention shall be subject to the attached claims.

Claims

1. A method for preparing a hydrogen evolution electrode, characterized in that: The following steps are involved: preparing an active component solution containing tris(2,2'-bipyridyl)ruthenium dichloride; Repeatedly brushing the active component solution on the surface of the conductive substrate for multiple times, and vacuum drying at a certain temperature after each brushing to form a multi-layer coating structure; Then, heat treatment is performed under an inert atmosphere to obtain the hydrogen evolution electrode.

2. The preparation method according to claim 1, characterized in that: The active component solution is prepared by dissolving the active component of tris(2,2'-bipyridine)ruthenium dichloride in an appropriate amount of solvent, and the concentration of the obtained tris(2,2'-bipyridine)ruthenium dichloride is 0.03-0.3 mol / L; The solvent comprises deionized water, glycerol, solvent A and solvent B, wherein the solvent A and solvent B are selected from any one of ethanol, isopropanol, n-butanol, tetrahydrofuran, acetone, ethyl acetate and ethylene glycol, and the volume ratio of the deionized water, glycerol, solvent A and solvent B is 1 to 4: 0.1~1:1~2:1~2。 3. The preparation method according to claim 1 or 2, characterized in that: The active component solution also contains 1 wt% to 10 wt% of a hydrophobic polymer. The hydrophobic polymer is polytetrafluoroethylene or polyvinylidene fluoride dissolved in N,N-dimethylformamide.

4. The preparation method according to claim 1, characterized in that: The vacuum drying temperature is 60-100°C, the duration is 2-5 hours, and the number of brushing times is 5-10 times; and / or, The heat treatment is carried out at a temperature of 400 to 900° C. and for a time of 2 to 10 hours.

5. The preparation method according to claim 1, characterized in that: Also included is a cleaning step for the conductive substrate: The conductive substrate is ultrasonically cleaned with appropriate amounts of sulfuric acid, anhydrous ethanol, and deionized water in sequence, and then vacuum dried for later use.

6. The preparation method according to claim 5, characterized in that: The concentration of the sulfuric acid is 0.1-1 mol / L, the duration of each ultrasonic cleaning is 5-20 minutes, the drying temperature after cleaning is 60-100° C., and the drying time is 1-5 hours.

7. The preparation method according to any one of claims 1 to 6, characterized in that: The conductive substrate is selected from any one of nickel mesh, nickel foam, sintered nickel plate and nickel felt.

8. A hydrogen evolution electrode, characterized in that According to the preparation method according to any one of claims 1 to 7, the hydrogen evolution electrode is supported by a nickel substrate, and the surface is uniformly loaded with a ruthenium-based nanocatalyst by a multi-layer coating technology.

9. The hydrogen evolution electrode according to claim 8, characterized in that A hydrophobic polymer is also introduced into the surface coating of the hydrogen evolution electrode to form a microscopic hydrophobic channel structure inside the electrode.

10. Application of a hydrogen evolution electrode in hydrogen production by electrolysis of water, characterized in that: The hydrogen evolution electrode according to claim 8 or 9, or the hydrogen evolution electrode prepared by the preparation method according to any one of claims 1 to 7, is used as a cathode in an alkaline medium to electrolyze water to produce hydrogen.